Percursos cartográficos e histórias vividas: a exploração sexual comercial de crianças e adolescentes em Foz do Iguaçu - PR - Neves, Thalita Rafaela (2015)
The commercial sexual exploration of children and teenagers is a phenomenon that happens in a secret and masked way. It allows that many young people are exposed to diseases, drugs use and others expressions of violence. The Foz do Iguaçu - PR area it belongs to Tríplice Fronteira betweens Paraguay, Argentina and Brazil. We studied the commercial sexual exploitation in Foz do Iguaçu, a tourism town that is located on the border. We contacted professionals who combated the sexual violence and the young people who have been involved. The search was conducted by the Cartographic method. We have seen that there is a failure in the Community Development in the city, as well as children and teenagers without access to information about their rights and dignity.